2017
DOI: 10.1039/c7sc00703e
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the polytopal rearrangements in penta-coordinate d7-metallocomplexes: modified Berry pseudorotation, octahedral switch, and butterfly isomerization

Abstract: New rearrangement mechanism prototypes are introduced to account for the non-ideal coordination and fluxional behavior of five-coordinate metalo-complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Finally, the process requires isomerization from the five‐coordinate species I3 to I3* before the rest of the process progresses symmetrically. The isomerization of five‐coordinate species has been extensively studied theoretically, which has shown that many reaction pathways are possible with activation energies within 10 kcal mol −1 . Using COPASI, we estimated the energy of the transition state TS3 to be 8.5 kcal mol −1 higher than I3 (Δ G ≠ =22.3 kcal mol −1 ).…”
Section: Figurementioning
confidence: 99%
“…Finally, the process requires isomerization from the five‐coordinate species I3 to I3* before the rest of the process progresses symmetrically. The isomerization of five‐coordinate species has been extensively studied theoretically, which has shown that many reaction pathways are possible with activation energies within 10 kcal mol −1 . Using COPASI, we estimated the energy of the transition state TS3 to be 8.5 kcal mol −1 higher than I3 (Δ G ≠ =22.3 kcal mol −1 ).…”
Section: Figurementioning
confidence: 99%
“…Moreover, the present results are in line with the finding, in solution, of a minor species, 3’ , identified at 193 K in the 31 P{ 1 H} NMR spectrum, that could now be ascribed to the calculated conformer 3 ζs , see Figure 6. Low‐barrier interconversion between these two ideal structures, leading to stereochemical non‐rigidity in solution, is frequent in five‐coordinated compounds [35] …”
Section: Resultsmentioning
confidence: 99%
“…[23] The dihedral angle between the plane including the pyrazole ligand with the NÀ H group and the plane formed by the coordinated acyl atoms C10 and O1, the metal centre Rh1 and the coordinated atoms N1, N2 and Cl1' of 8.4°is consistent with the existence of an intramolecular hydrogen bond. [24] The 35 ppm suggest a metallotropic tautomerism of the other pyrazole with fast exchange of the metal and the proton bonded to the nitrogen atoms. [15a,25] Lowering the temperature down to 233 K results in sharpening of these resonances and confirms the proposed metallotropy ( Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…This first step has an energy barrier of 20.3 kcal mol À1 and gives rise to the octahedral complex I2,i nw hich the Au atom is in the axial position and the Pf moiety is in the equatorial plane, cis to the Rf group.F rom I2,calculations indicate that the dissociation of the arsine ligand in the axial position to afford the fivecoordinate intermediate I3 is almost thermoneutral. [15] Using COPASI, we estimated the energy of the transition state TS3 to be 8.5 kcal mol À1 higher than I3 (DG°= 22.3 kcal mol À1 ). Estimations of coordination transition states in the literature suggest areasonable value about 4.5 kcal mol À1 higher than I3,owing to diffusion cost in solution.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Theisomerization of five-coordinate species has been extensively studied theoretically,w hich has shown that many reaction pathways are possible with activation energies within 10 kcal mol À1 . [15] Using COPASI, we estimated the energy of the transition state TS3 to be 8.5 kcal mol À1 higher than I3 (DG°= 22.3 kcal mol À1 ).…”
Section: Zuschriftenmentioning
confidence: 99%